Alterations in Body Composition, Resting Metabolic Rate, Muscular Strength, and Eating Behavior in Response to Natural Bodybuilding Competition Preparation: A Case Study. Issue 11 (November 2020) - Schoenfeld, Brad J.; Alto, Andrew; Grgic, Jozo; Tinsley, Grant; Haun, Cody T.; Campbell, Bill I.; Escalante, Guillermo; Sonmez, Gul T.; Cote, Gilda; Francis, Aston; Trexler, Eric T.
Abstract : Abstract: Schoenfeld, BJ, Alto, A, Grgic, J, Tinsley, G, Haun, CT, Campbell, BI, Escalante, G, Sonmez, GT, Cote, G, Francis, A, and Trexler, ET. Alterations in body composition, resting metabolic rate, muscular strength, and eating behavior in response to natural bodybuilding competition preparation: A case study. J Strength Cond Res 34(11): 3124–3138, 2020—We carried out a prospective case study in a high-level amateur natural male bodybuilder throughout preparation for 4 competitions and during the ensuing postcontest recovery period. Laboratory testing was conducted monthly over a 1-year period, which included the following assessments: B-mode ultrasound evaluation of muscle thickness (MT), multifrequency bioelectrical impedance analysis, blood pressure and heart rate assessment, resting metabolic rate via indirect calorimetry, skinfold testing, vertical jump height, isometric lower-body strength testing, and a 3-factor eating questionnaire. Blood work (including testosterone, thyroid hormone, sex hormone binding globulin, glomerular filtration rate, blood urea nitrogen, aspartate aminotransferase, alanine aminotransferase, white blood count, albumin to globulin ratio, and lipoprotein A) was obtained separately from an outside laboratory at 4 time points. We also assessed the effectiveness of a carbohydrate (carb) deplete and carb load peaking strategy employed immediately before competition. The subject employed a high-volume, high-frequency, whole-body training program throughout the study period. Average daily nutritional intakes ranged from 1, 953 to 3, 415 kcal: 104–386 g carb; 253–263 g protein, and; 57–95 g lipid. Body fat was reduced to very low levels (∼5%) immediately before competition, but this corresponded with a loss of lean mass. Alterations in metabolism, hormonal status, explosive strength, and psychological aspects of eating were observed during precontest preparation; however, all of these variables recovered quickly postcompetition. The implementation of a carb depleteand carb load peaking strategy acutely increased MT and thus may be a viable precontest approach to maximize muscular aesthetics.